Stalking – Criminological and Criminal Justice Aspects - Kovačević, Milica; Maljković, Marija (Zbornik Instituta za kriminološka i sociološka istraživanja, 2016)
Stalking is related to continuous monitoring, invasion of privacy or harassment of certain persons, which endangers security or creates a sense of anxiety for the victim. Given that undertaken actions may not be illegal per se, that raises the question of how to prevent stalking without extensive restriction of the rights and freedoms of citizens, at the same time. Therefore, this paper presents criminological and criminal justice aspects of stalking, as well as the results of studies which indicate the seriousness of the consequences and social risks of stalking, in order to point out different types of reactions to this phenomenon. The authors conclude that there is a need for the introduction of the offence of stalking in Serbia, but that other forms of reaction are also necessary.